2017
DOI: 10.18203/2320-6012.ijrms20174601
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of high energy tibial plateau fractures with hybrid external fixator: intermediate term outcome

Abstract: Background: High energy tibial plateau fractures pose a management challenge because of the complexity of bone and soft tissue trauma. Because of the frequency and magnitude of soft tissue of soft tissue injury in these fractures, early internal fixation becomes difficult. Wound breakdown and deep infection are common complications in plating of these difficult fractures. Primary management with hybrid external fixator can be a useful alternative to internal fixation in such cases.Methods: The study was a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…The development of Ilizarov frame increased the capability of axial compression with dynamization around the fracture site with respect to the associated soft tissue injuries. The development of olive wires has offered new likelihoods to the external fixators for the management of complex fractures (7) In agreement with the present work, Jahan et al (8) performed a study on 20 patients, 13 Schatzker VI, 5 Schatzker V and 2 Schatzker IV fractures. In addition, there were 4 patients with open fractures and one patient had compartment syndrome.…”
Section: Discussionsupporting
confidence: 86%
“…The development of Ilizarov frame increased the capability of axial compression with dynamization around the fracture site with respect to the associated soft tissue injuries. The development of olive wires has offered new likelihoods to the external fixators for the management of complex fractures (7) In agreement with the present work, Jahan et al (8) performed a study on 20 patients, 13 Schatzker VI, 5 Schatzker V and 2 Schatzker IV fractures. In addition, there were 4 patients with open fractures and one patient had compartment syndrome.…”
Section: Discussionsupporting
confidence: 86%
“…The present study finding showed that the majority of the control group and all patients participant in study group were males. This study result was supported by Jahan et al, (2017) confirmed that more than half of studied patients were males. From the researchers' point of view, males are more likely to expose to occupational trauma when they are expected to support and meet the financial needs of their families in current society.…”
Section: Discussionsupporting
confidence: 83%
“…21 Jahan et al in 2017 had excellent results in 15 patients and fair in 4 patients. 22 In our study, 20 26 Bari et al in 2014 operated on 40 patients with Ilizarov external fixator and had 28 patients with excellent, 9 patients with good, 2 with fair and 1 patient with poor results. 27 Aziz et al in 2016 operated on 20 patients, 18 had excellent and good results, poor in 2 patients.…”
Section: Study Of Hybrid Fixation Of Tibial Plateau Fractures Bymentioning
confidence: 48%
“…Mean time for radiological union in patients treated by Ilizarov fixator was 24.5 weeks (range 15 to 32 weeks) and in patients treated by hybrid fixator was 28 weeks. Mean fixator period was 26 weeks (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) week) in Ilizarov and 30 week in hybrid fixator. Both the fixators were removed after 2 weeks of union ( Figure 7).…”
Section: Resultsmentioning
confidence: 99%